E-LEARNING LEARNING ANALYSIS TOWARDS LEARNING OUTCOMES OF STUDENTS DEPARTMENT OF BUILDING ENGINEERING EDUCATION, STATE UNIVERSITY OF MANADO - SANDI ARAFA MOKOBOMBANG SANDI; Djubir Kembuan; metsi daud; I Wayan Semueil; Titof Tulaka (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
The purpose of this research is to use a quantitative research approach using a deductive-inductive approach. This approach departs from a theoretical framework, the ideas of experts, as well as the understanding of researchers based on their experiences, then developed into problems proposed to obtain justification in the form of field empirical data. The population in this study were all PTB students, totaling 170 students. The sample obtained by using the formula is 63 students of the Department of Building Engineering Education. The results of hypothesis testing indicate that there is a significant influence between e-learning learning on student learning outcomes in the Department of Building Engineering Education, Faculty of Engineering, Manado State University. Based on the results of the analysis that has been done, it can be seen that the coefficient of the determinant variable (r²) is 0.289 or 28.9%. This indicates that e-learning has an effect on student learning outcomes of the Department of Building Engineering Education, Faculty of Engineering, Manado State University as much as 28.9%. While the remaining 71.1% is influenced by other variables not examined in this study. Thus, the higher or better the E-Learning Learning, the higher the Student Learning Outcomes. Conversely, the lower the E-Learning Learning, the lower the Student Learning Outcomes. Keywords: E-Learning Learning and Learning Outcomes.